Bibliographie der Elateridenlarven-Literatur der Welt. - Gaedike, Reinhard (Contributions to Entomology = Beiträge zur Entomologie, 1969)
A bibliography of international publications on the larvae of elaterids up to 1967 is presented. A total of 1519 titles are listed and, if possible, annotated. Indexes of subjects and species faciliate the use of this bibliography.